Удмуртский язык: становление и развитие: сборник статей / И. В. Тараканов - Тараканов Иван Васильевич (Удмуртия, 2007)
Экземпляры: СФ-3 (20121121) / Инвентарный номер: 36010z3 / Цена: 160.00 / Сис.шифр: 81.2Удм / Авт.знак: Т 19 / ГРНТИ: 16.41.25 / ББК: 81.2Удм